A negative electrode material and its preparation method and application

By heat treatment and crushing the mixture of silicon powder, titanium dioxide and asphalt, and mixing with graphite for granules and carbonization, prepare negative materials with excellent circulation performance and high discharge capacity, solving existing lithium ion battery negative electrode materials Insufficient performance.

CN116495722BActive Publication Date: 2025-01-28河南中炭新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310546591.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2025-01-28
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

The negative electrode material circulation and discharge capacity of existing lithium-ion batteries are relatively low, making it difficult to meet the needs of future battery performance improvement.

Method used

By heat treatment and crushing of silicon powder, titanium dioxide and asphalt mixture, the unspeakable treatment is obtained, and granulation and carbonization treatment with graphite is obtained, and negative materials with excellent circulation performance and high discharge capacity are prepared.

Benefits of technology

This method is simple and easy, the obtained negative material has excellent circulation performance and high discharge capacity, which significantly improves the overall performance of lithium -ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular, to a negative electrode material and a preparation method and application thereof. The preparation method of the negative electrode material of the present invention comprises the following steps: heat-treating and pulverizing a mixture of silicon powder, titanium dioxide and asphalt to obtain a coating material, and granulating and carbonizing the mixture of the coating material and graphite. The method is simple and easy to implement, and the obtained negative electrode material has excellent cycle performance and high discharge capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used and studied for their high operating voltage, high energy density, good safety performance, and no pollution. Lithium-ion batteries are generally composed of positive electrode materials, negative electrode materials, separators, and electrolytes, among which the negative electrode materials are mainly carbon. However, their theoretical specific capacity is low, at 372mAh / g, and there is limited room for future development, so the development of mixed negative electrode materials is crucial.

[0003] At present, graphite is still the mainstream in the market, but graphite itself has defects and many side reactions. Silicon-carbon negative electrode is an important way to improve the energy density of lithium batteries. The theoretical specific capacity of silicon is 4200mAh / g, which is more than ten times that of graphite negative electrode. Its delithiation potential is relatively low (0.4V), but the volume of silicon negative electrode expands greatly during the cycle. After full lithium insertion, the volume expansion is 320%. It is easy to pulverize and fail during the lithium insertion and deintercalation process. Coating and carbonization technology can modify the negative electrode material and reduce the expansion of silicon negative electrode.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] An object of the present invention is to provide a method for preparing a negative electrode material to solve the technical problems of low cycle performance and discharge capacity of lithium-ion batteries made from negative electrode materials in the prior art; the method is simple and easy to implement, and the obtained negative electrode material has excellent cycle performance and high discharge capacity.

[0006] Another object of the present invention is to provide a negative electrode material prepared by the negative electrode material preparation method.

[0007] Another object of the present invention is to provide a negative electrode sheet comprising the negative electrode material.

[0008] Another object of the present invention is to provide a battery, comprising the negative electrode sheet.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A method for preparing a negative electrode material comprises the following steps:

[0011] The mixture of silicon powder, titanium dioxide and asphalt is subjected to heat treatment and pulverization to obtain a coating material, and the mixture of the coating material and graphite is subjected to granulation and carbonization.

[0012] Preferably, the particle size D50 of the silicon powder is ≤0.2 μm.

[0013] Preferably, the particle size D50 of the titanium dioxide is ≤0.2 μm.

[0014] Preferably, the particle size D50 of the graphite is 8 to 20 μm.

[0015] Preferably, the mass ratio of the silicon powder, the titanium dioxide and the asphalt is (0.1-1):(0.05-0.5):1, preferably (0.3-0.8):(0.1-0.4):1.

[0016] Preferably, the mass ratio of the graphite to the coating material is 1:(0.05-0.15), preferably 1:(0.09-0.12).

[0017] Preferably, the asphalt comprises petroleum asphalt.

[0018] Preferably, the temperature of the heat treatment is 150-200° C., and the time of the heat treatment is 2-6 hours.

[0019] Preferably, the temperature of the heat treatment is 180-190° C., and the time of the heat treatment is 3-4 hours.

[0020] Preferably, the pulverizing process pulverizes the coating material to a particle size D50 of 1 to 3 μm.

[0021] Preferably, the granulation temperature is 200-600° C., and the granulation time is 2-6 hours.

[0022] Preferably, the granulation temperature is 300-400° C., and the granulation time is 3-4.5 h.

[0023] Preferably, the carbonization temperature is 1000-1400° C., and the carbonization time is 6-16 hours.

[0024] Preferably, the carbonization temperature is 1100-1300° C., and the carbonization time is 7-10 h.

[0025] In the method for preparing the negative electrode material, the material obtained after granulation is subjected to a second pulverization process.

[0026] Preferably, the material after the carbonization treatment is subjected to a third pulverization treatment, a screening treatment and a demagnetization treatment in sequence.

[0027] Preferably, the heat treatment and the granulation are respectively performed under protective gas conditions.

[0028] The negative electrode material is prepared by the negative electrode material preparation method.

[0029] A negative electrode sheet comprises the negative electrode material.

[0030] A battery comprises the negative electrode sheet.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The preparation method of the negative electrode material of the present invention is simple and easy, and the obtained negative electrode material has excellent cycle performance and high discharge capacity.

[0033] (2) The negative electrode adopts a negative electrode material to improve the electrochemical performance; the battery prepared therefrom has the advantages of high discharge capacity and high cycle performance. DETAILED DESCRIPTION

[0034] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0035] According to one aspect of the present invention, the present invention relates to a method for preparing a negative electrode material, comprising the following steps:

[0036] The mixture of silicon powder, titanium dioxide and asphalt is subjected to heat treatment and pulverization to obtain a coating material, and the mixture of the coating material and graphite is subjected to granulation and carbonization.

[0037] In the present invention, anatase titanium dioxide (TiO2) has good coating potential due to its low expansion rate, high mechanical stability, high electron ion transportability when lithium is inserted and removed, and excellent electrochemical reversibility. The highly crystalline TiO2 layer is dense and uniform, which can improve the interface stability. It can not only serve as a buffer layer to effectively reduce the impact damage of internal stress on the structure, but also provide an efficient transmission channel to accelerate ion and electron transfer, improve electrode kinetic behavior, and at the same time, it can serve as a protective layer to significantly increase the side reaction energy barrier and enhance the side reaction resistance, and can also improve the overall safety of the electrode. Coating the nano titanium dioxide layer is conducive to the formation of a shell structure, and titanium dioxide effectively prevents the expansion of graphite. The present invention can obtain a negative electrode material with high discharge capacity and excellent cycle performance through specific operating steps.

[0038] Preferably, the particle size D50 of the silicon powder is ≤ 0.2 μm. In one embodiment, the particle size D50 of the silicon powder includes but is not limited to 0.01 μm, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.11 μm, 0.15 μm, 0.16 μm or 0.18 μm.

[0039] Preferably, the particle size D50 of the titanium dioxide is ≤ 0.2 μm. In one embodiment, the particle size D50 of the titanium dioxide includes but is not limited to 0.01 μm, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.11 μm, 0.15 μm, 0.16 μm or 0.18 μm.

[0040] Preferably, the particle size D50 of the graphite is 8 to 20 μm. The particle size D50 of the graphite includes but is not limited to 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, and 19 μm.

[0041] Preferably, the mass ratio of the silicon powder, the titanium dioxide and the asphalt is (0.1-1):(0.05-0.5):1. Preferably, it is (0.3-0.8):(0.1-0.4):1.

[0042] In one embodiment, the mass ratio of the silicon powder, the titanium dioxide and the asphalt includes but is not limited to 0.1:0.08:1, 0.5:0.4:1, and 1:0.5:1. The silicon powder, the titanium dioxide and the asphalt of the present invention are in a suitable mass ratio, thereby improving the electrochemical performance of the coating material, and the negative electrode material obtained by compounding with graphite later has excellent rate performance and cycle performance.

[0043] Preferably, the mass ratio of the graphite to the coating material is 1:(0.05-0.15), preferably 1:(0.09-0.12). In one embodiment, the mass ratio of the graphite to the coating material includes but is not limited to 1:0.06, 1:0.08, 1:0.1, 1:0.12, 1:0.14. In the present invention, the mass ratio of the graphite to the coating material is within an appropriate range to obtain a negative electrode material with high cycle performance and high rate performance. If the ratio is too high or too low, a negative electrode material with excellent cycle performance and rate performance cannot be obtained.

[0044] Preferably, the asphalt comprises petroleum asphalt. Petroleum asphalt is a product of crude oil processing, which is a black or dark brown viscous liquid, semi-solid or solid at room temperature, and mainly contains hydrocarbons and non-hydrocarbon derivatives soluble in trichloroethylene. In one embodiment, the petroleum asphalt is medium-temperature petroleum asphalt.

[0045] Preferably, the temperature of the heat treatment is 150-200° C., and the time of the heat treatment is 2-6 hours.

[0046] In one embodiment, the heat treatment temperature includes but is not limited to 155°C, 160°C, 165°C, 170°C, 180°C, 185°C, 190°C or 195°C. The heat treatment time includes but is not limited to 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or 5.5h. The present invention improves the performance of the coating material by matching the appropriate heat treatment temperature and heat treatment time.

[0047] Preferably, the heat treatment temperature is 180-190° C., and the heat treatment time is 3-4 hours. By further optimizing the heat treatment temperature and time, the electrochemical performance of the negative electrode material can be further improved.

[0048] Preferably, the pulverization process pulverizes the coating material to a particle size D50 of 1 to 3 μm. In one embodiment, the pulverization process pulverizes the coating material to a particle size D50 including but not limited to 1.2 μm, 1.5 μm, 1.7 μm, 2 μm, 2.2 μm, 2.5 μm, 2.7 μm or 2.9 μm.

[0049] Preferably, the granulation temperature is 200-600°C, and the granulation time is 2-6 hours. In one embodiment, the granulation temperature includes but is not limited to 210°C, 220°C, 230°C, 240°C, 250°C, 300°C, 320°C, 350°C, 400°C, 450°C, 500°C or 550°C. The granulation time includes but is not limited to 2.5 hours. The present invention can improve the cycle performance and discharge gram capacity of the negative electrode material by adopting appropriate granulation temperature and time.

[0050] Preferably, the granulation temperature is 300-400° C., and the granulation time is 3-4.5 h.

[0051] Preferably, the carbonization temperature is 1000-1400°C, and the carbonization time is 6-16h. In one embodiment, the carbonization temperature includes but is not limited to 1050°C, 1100°C, 1120°C, 1150°C, 1180°C, 1200°C, 1220°C, 1250°C, 1280°C, 1300°C, 1340°C or 1380°C. The carbonization time includes but is not limited to 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h.

[0052] The carbonization treatment is carried out in a box-type atmosphere furnace.

[0053] Preferably, the carbonization temperature is 1100-1300° C., and the carbonization time is 7-10 h.

[0054] Preferably, the material obtained after the granulation is subjected to a second pulverization treatment.

[0055] Preferably, the material after the carbonization treatment is subjected to a third pulverization treatment, a screening treatment and a demagnetization treatment in sequence.

[0056] Preferably, the heat treatment and the granulation are respectively performed under protective gas conditions.

[0057] The protective gas includes nitrogen, inert gas such as helium, etc.

[0058] According to another aspect of the present invention, the present invention relates to a negative electrode material prepared by a method for preparing a negative electrode material.

[0059] According to another aspect of the present invention, the present invention relates to a negative electrode sheet, comprising the negative electrode material.

[0060] According to another aspect of the present invention, the present invention relates to a battery, comprising the negative electrode sheet.

[0061] The present invention will be further explained below with reference to specific embodiments and comparative examples.

[0062] Example 1

[0063] A method for preparing a negative electrode material comprises the following steps:

[0064] The silicon material was sand-ground to a silicon powder with a particle size D50 of 0.15 μm, and the TiO2 was sand-ground to a grain size D50 of 0.18 μm. Then, the silicon powder, TiO2, and asphalt were evenly mixed in a mass ratio of 0.5:0.5:1, and high-temperature kneading was carried out at 150°C in a nitrogen atmosphere for 3 hours. After cooling, air flow crushing was carried out to prepare a coating material with a particle size D50 of 2.0 μm. Then, high-temperature granulation was carried out with graphite crushed in a mass ratio of 1:0.1 in a nitrogen atmosphere at 550°C for 4 hours. The D50 of the crushed graphite crushed was 14 μm. After being broken up, high-temperature carbonization was carried out at 1150°C in a box-type atmosphere furnace for 16 hours. After being broken up, it was sieved and demagnetized to prepare a lithium-ion battery hybrid negative electrode material.

[0065] Example 2

[0066] A method for preparing a negative electrode material comprises the following steps:

[0067] The silicon material is sand-ground to a silicon powder with a particle size D50 of 0.2 μm, and the TiO2 is sand-ground to a grain size D50 of 150 nm. Then, the silicon powder, TiO2, and asphalt are evenly mixed in a mass ratio of 0.1:0.05:1, and high-temperature kneading is carried out at 180°C in a nitrogen atmosphere for 6 hours. After cooling, air flow crushing is carried out to prepare a coating material with a particle size D50 of 1.9 μm. Then, high-temperature granulation is carried out with graphite fragments in a mass ratio of 1:0.05 in a nitrogen atmosphere at 600°C for 3 hours. The D50 of the graphite fragments after crushing is 10 μm. After being broken up, high-temperature carbonization is carried out at 1300°C for 12 hours in a box-type atmosphere furnace. After being broken up, it is sieved and demagnetized to prepare a lithium-ion battery mixed negative electrode material.

[0068] Example 3

[0069] A method for preparing a negative electrode material comprises the following steps:

[0070] The silicon material is sand-ground to a silicon powder with a particle size D50 of 0.10 μm, and the TiO2 is sand-ground to a grain size D50 of 200 nm. Then, the silicon powder, TiO2, and asphalt are evenly mixed in a mass ratio of 0.3:0.2:1, and high-temperature kneading is carried out at 200°C in a nitrogen atmosphere for 4 hours. After cooling, it is air-flow crushed to prepare a coating material with a particle size D50 of 2.1 μm. Then, it is high-temperature granulated with graphite fragments in a mass ratio of 1:0.15 in a nitrogen atmosphere at 400°C for 6 hours. The graphite fragments after crushing have a D50 of 15 μm. After being dispersed, they are high-temperature carbonized at 1100°C for 12 hours in a box-type atmosphere furnace. After being dispersed, they are sieved and demagnetized to prepare a lithium-ion battery hybrid negative electrode material.

[0071] Comparative Example 1

[0072] A method for preparing a negative electrode material, except that the mass ratio of silicon powder, TiO2 and asphalt is 0.03:0.02:1.95, other conditions are the same as those in Example 1.

[0073] Comparative Example 2

[0074] A method for preparing a negative electrode material, wherein the mass ratio of graphite fragments to coating material is 1:0.03, and other conditions are the same as those in Example 1.

[0075] Comparative Example 3

[0076] A method for preparing a negative electrode material, wherein the high-temperature mixing temperature is 130° C. and the mixing time is 1.5 h, and other conditions are the same as those in Example 1.

[0077] Comparative Example 4

[0078] A method for preparing a negative electrode material, except that the temperature of high-temperature granulation is 180° C. and the time is 1.5 h, other conditions are the same as those in Example 1.

[0079] Comparative Example 5

[0080] A method for preparing a negative electrode material, except that the high-temperature carbonization temperature is 900° C. and the time is 5 hours, and other conditions are the same as those in Example 1.

[0081] Experimental example

[0082] The negative electrode materials of the embodiment and the comparative example are used to prepare a battery, and the preparation method comprises the following steps:

[0083] (1) Use a high-speed disperser to add 1.5wt% CMC solution and SP, stir at 2000r / min for 10min, adjust the speed to 200r / min, add negative electrode material, stir at 2000r / min for 90min, add 50% SBR solution, stir for 10min, sieve, and apply. The coating thickness is 150μm. The mass ratio of each component is: negative electrode material: CMC: SP: SBR = 93:1.5:2.0:3.5.

[0084] (2) Drying: Dry at 60°C for 4 h and then at 110°C for 2 h.

[0085] (3) Weighing of roller-pressed cut pieces: Adjust the roller press to control the compaction density of the pole piece to >1.5g / cm 3 , cut into 14mm diameter electrodes, weigh and vacuum dry for 4h.

[0086] (4) Assembly: Weigh the electrode again and assemble in the glove box. The assembly order is: negative electrode shell - 1 drop of electrolyte - electrode - 3 drops of electrolyte - diaphragm - 3 drops of electrolyte - lithium sheet - gasket - spring - positive electrode shell, and seal.

[0087] (5) Blue battery test: Test procedure 0.05C, 0.05mA 0.02mA discharge, 0.1C charge.

[0088] The obtained battery was subjected to performance testing, and the results are shown in Table 1.

[0089] Table 1 Performance test results

[0090] Examples and Comparative Examples Gram capacity (mAh / g) First effect (%) Example 1 375 93.5 Example 2 370 93.7 Example 3 380 93.8 Comparative Example 1 352 93.1 Comparative Example 2 355 93.3 Comparative Example 3 353 93.2 Comparative Example 4 356 93.0 Comparative Example 5 352 92.9

[0091] As can be seen from Table 1, the negative electrode material obtained by the present invention has excellent capacity through the combination of specific operating steps and parameter conditions; the battery prepared by the negative electrode material has excellent cycle performance. The mass ratio of silicon powder, TiO2, and asphalt in Comparative Example 1 is not within the protection scope of the present invention, the mass ratio of graphite fragments to coating materials in Comparative Example 2 is not within the protection scope of the present invention, the temperature and time of high-temperature mixing in Comparative Example 3 are not within the protection scope of the present invention, the temperature and time of high-temperature granulation in Comparative Example 4 are not within the protection scope of the present invention, and the temperature and time of high-temperature carbonization in Comparative Example 5 are not within the protection scope of the present invention. The capacity of the obtained negative electrode material is worse than that of Example 1.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a negative electrode material, characterized in that: The following steps are involved: The mixture of silicon powder, titanium dioxide and asphalt is subjected to heat treatment and pulverization to obtain a coating material, and the mixture of the coating material and graphite is subjected to granulation and carbonization.

2. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size D50 of the silicon powder is ≤0.2 μm.

3. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size D50 of the titanium dioxide is ≤0.2 μm.

4. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size D50 of the graphite is 8-20 μm.

5. The method for preparing the negative electrode material according to claim 1, characterized in that: The mass ratio of the silicon powder, the titanium dioxide and the asphalt is (0.1~1):(0.05~0.5):

1.

6. The method for preparing the negative electrode material according to claim 5, characterized in that: The mass ratio of the silicon powder, the titanium dioxide and the asphalt is (0.3~0.8):(0.1~0.4):

1.

7. The method for preparing the negative electrode material according to claim 1, characterized in that: The mass ratio of the graphite to the coating material is 1:(0.05-0.15).

8. The method for preparing the negative electrode material according to claim 7, characterized in that: The mass ratio of the graphite to the coating material is 1:(0.09-0.12).

9. The method for preparing the negative electrode material according to claim 1, characterized in that: The asphalt includes petroleum asphalt.

10. The method for preparing the negative electrode material according to claim 1, characterized in that: The temperature of the heat treatment is 150-200° C., and the time of the heat treatment is 2-6 hours.

11. The method for preparing the negative electrode material according to claim 10, characterized in that: The temperature of the heat treatment is 180-190° C., and the time of the heat treatment is 3-4 hours.

12. The method for preparing the negative electrode material according to claim 1, characterized in that: The pulverizing process pulverizes the coating material until the particle size D50 is 1-3 μm.

13. The method for preparing the negative electrode material according to claim 1, characterized in that: The granulation temperature is 200-600° C., and the granulation time is 2-6 hours.

14. The method for preparing the negative electrode material according to claim 13, characterized in that: The granulation temperature is 300-400° C., and the granulation time is 3-4.5 hours.

15. The method for preparing the negative electrode material according to claim 1, characterized in that: The carbonization temperature is 1000-1400° C., and the carbonization time is 6-16 hours.

16. The method for preparing the negative electrode material according to claim 15, characterized in that: The carbonization temperature is 1100-1300° C., and the carbonization time is 7-10 hours.

17. The method for preparing a negative electrode material according to any one of claims 1 to 16, characterized in that: The material obtained after the granulation is subjected to a second pulverization process.

18. The method for preparing a negative electrode material according to any one of claims 1 to 16, characterized in that: The carbonized material is sequentially subjected to a third pulverizing process, a screening process and a demagnetization process.

19. The method for preparing a negative electrode material according to any one of claims 1 to 16, characterized in that: The heat treatment and the granulation are respectively carried out under protective gas conditions.

20. The negative electrode material prepared by the method for preparing a negative electrode material according to any one of claims 1 to 19.

21. A negative electrode sheet, characterized in that: Comprising the negative electrode material as claimed in claim 20.

22. A battery, characterized in that: Includes the negative electrode sheet as described in claim 21.

Citation Information

Patent Citations

  • Preparation method of modified lithium titanate negative material of lithium-ion battery

    CN103296257A

  • Preparation method for silicon-based negative electrode material, negative electrode material and battery

    CN105789576A